Utilization of biochar derived from industrial hemp stalks with various cooling methods for asphalt binder modification - İbrahim Aslan; Funda Tasdemir; Yuksel Tasdemir (PLoS ONE, 2025)
The study aimed to identify the optimum pyrolysis temperature and cooling conditions for producing biochar from industrial hemp stalks to enhance asphalt binder performance, while also assessing the potential of industrial hemp stalks as a viable alternative in the pavement sector by evaluating the temperature sensitivity and the high and low temperature performance of biochar-modified binders. The asphalt binders were subjected to conventional and performance tests to assess their properties. Penetration and softening point values of neat and biochar modified binders were determined and the penetration index of binders was calculated. The temperature susceptibility, permanent deformation, aging and fatigue performances of neat and biochar modified asphalt binders were determined by the dynamic shear rheometer test. Bending beam rheometer equipment was used to determine the low temperature performance of asphalt binders. The experimental results showed that biochar obtained from industrial hemp stalk improved aging resistance, reduced the temperature susceptibility, increased high-temperature performance grade, and so developed permanent deformation resistance of the binder. The optimal production conditions for biochar, utilized in the modification of asphalt binders to achieve better rutting resistance, have been identified as a combination of a pyrolysis temperature of 300°C and rapid cooling. The low-temperature performance grade of biochar-modified asphalt binders decreased by one grade, while the high-temperature performance grade increased by at least one grade. The addition of biochar was shown to have a negative impact on the binder’s low-temperature performance. Based on these findings, it was concluded that the biochar additive, derived from industrial hemp stalk, is particularly well-suited for regions characterized by hot climates.